Resistance patterns of multidrug resistant Acinetobacter baumannii in an ICU of a tertiary care hospital, Malaysia - Janahiraman, Sivakami (Pak J Med Sci, 2015)
BACKGROUNDS & OBJECTIVE: Antimicrobial resistance is a major health problem worldwide in hospitals. The main contributing factors are exposures to broad-spectrum antimicrobials and cross-infections. Understanding the extent and type of antimicrobial use in tertiary care hospitals will aid in developing national antimicrobial stewardship priorities. METHODS: In this study, we have analyzed the antimicrobial agents’ usage for acquisition of multidrug resistant using retrospective, cross-sectional, single-centre study in a multidisciplinary ICU at tertiary care hospital. RESULTS: Acinetobacter baumannii (ACB) was isolated in various specimens from 662 patients. From these, 136 patients who were diagnosed with Ventilator-associated pneumonia (VAP) caused by ACB were included into the study. In our study, MDR strain accounts for 51% of all VAP cases caused by ACB. The development of ACB VAP were 10.5 + 6.4 days for MDR strains compared to susceptible organism (7.8 + 4.5 days) and had significantly longer ICU stay. CONCLUSION: The study concludes that prudent use of antimicrobial agents is important to reduce acquisition of MDR ACB.